A nano silver wire conductive film
By preparing nano-silver wire conductive films on the same substrate, combining structural design and thickness refractive index matching, the problem of expensive equipment and low efficiency in the production process of existing ITO conductive films is solved, and the nano-silver wire conductive film with anti-glare and anti-reflection functions is realized, reducing production costs and improving user experience.
Patent Information
- Application Number
- CN201911271367.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-12-12
AI Technical Summary
The existing ITO conductive films require expensive coating equipment during the production process, with low production efficiency and large color difference. Indium in ITO is a rare metal, which will cause serious problems to social development after use.
By preparing nano-silver wire conductive films on the same substrate, combining structural design and thickness refractive index matching, an anti-glare layer and a nano-silver conductive layer are prepared, and an anti-reflective coating is applied to the anti-glare coating to enhance the anti-glare and anti-reflective functions.
The nano-silver wire conductive film with reduced production costs, improved production efficiency, and achieved anti-glare and anti-reflection functions, improving the user experience of consumers.
Smart Images

Figure CN111009337B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an optical film, in particular to a nano silver wire conductive film. Background Art
[0002] Before the invention, the main products used in capacitive touch screens on the market include double-sided hardened films, optical adjustment layers and ITO conductive films. These conductive film products can meet the basic needs of current capacitive touch screens. However, in the product preparation process, the above products first need to use a coating device to coat a layer of low refractive index layer (SiO2) on the double-sided hardened film, and then coat a layer of ITO conductive layer, followed by high-temperature crystallization of ITO. The coating equipment required in this production process is expensive, has low production efficiency, and has heavy color difference. In addition, we all know that the indium in ITO is a rare metal, and its reserves in the earth are very rare. Once such rare metals are used up, it will cause serious problems for the development of human society.
[0003] In the future, mobile terminals, wearable devices, smart home appliances and other products will have a strong demand for touch panels. At the same time, as touch panels become larger in size and lower in price, and traditional ITO films cannot be used for flexible applications, and inherent problems such as conductivity and transmittance are difficult to overcome, many panel manufacturers have begun to study alternatives to ITO.
[0004] Silver nanowires are nanomaterials with a diameter of 10-300nm and a length of 0.1-200μm that are chemically grown. In addition to the excellent conductivity of silver, silver nanowires also have excellent light transmittance and bending resistance due to the size effect at the nanoscale. Because it is considered to be the most likely material to replace the traditional ITO transparent electrode, it provides the possibility of realizing flexible and bendable LED displays, touch screens, etc., and a large number of studies have been conducted to apply it to thin-film solar cells. Silver nanowire (SNW) technology is to apply silver nanowire ink material on a plastic or glass substrate, and then use laser lithography technology to carve a transparent conductive film with a nanoscale silver wire conductive network pattern. Due to its special physical mechanism of manufacture, the diameter of the line width of the silver nanowire is very small, about 50nm, which is much smaller than 1um, so there is no problem of Murray interference, and it can be used on display screens of various sizes.
[0005] Nano silver wire conductive film has emerged in the market, but most of the nano silver wires are coated on PET substrates or PET hardened substrates. Two nano silver wire conductive films and an anti-glare film cover constitute the product structure required by the terminal. The specific structure of this product is lower nano silver wire conductive film, OCA, upper nano silver wire conductive film, OCA, and anti-glare film cover. Summary of the invention
[0006] The main purpose of the present invention is to provide a nano silver wire conductive film. Through structural design and thickness and refractive index matching, an anti-glare layer and a nano silver conductive layer are prepared on the same substrate, and an anti-reflection coating is coated on the anti-glare coating, thereby enhancing the anti-glare and anti-reflection functions, reducing production costs and improving production efficiency.
[0007] To achieve the above-mentioned purpose, the technical solution of the present invention is:
[0008] A nano silver wire conductive film comprises a substrate, a nano silver wire conductive layer, an anti-glare layer and a low refractive index layer.
[0009] Furthermore, the anti-glare layer has a thickness ranging from 5 to 18 μm.
[0010] Furthermore, the low refractive index layer has a thickness ranging from 80 to 120 nm.
[0011] Furthermore, the refractive index range of the low refractive index layer is 1.3-1.45. If the thickness is not within this range, the film material looks purple or green; the refractive index of the coating is 1.3-1.45. The minimum refractive index of organic resins (containing inorganic particles) that can be mass-produced on the market is greater than or equal to 1.3, and the refractive index is less than or equal to 1.45. The greater the refractive index of the material surface, the greater the reflectivity.
[0012] Furthermore, the diameter of the nano silver wire in the nano silver wire conductive layer is in the range of 10-30 nm, and the length is in the range of 10-100 μm. If the diameter of the nano silver wire is too small or the length is longer, the yield is very low in the actual production process of the silver wire, thereby increasing the production cost.
[0013] The method for synthesizing the nano silver wire is as follows:
[0014] At room temperature, 1-butyl-3-methylimidazolium platinum chloride (0.0215 g / 1 mL ethylene glycol solution) and PVP-430000 solution (0.3 g / 10 mL ethylene glycol solution) were added to 100 mL ethylene glycol solvent respectively, and the mixture was slowly stirred for 30 minutes. Then, silver nitrate solution (0.23 g / 10 mL ethylene glycol solution) was slowly added while stirring. After stirring for 40 minutes, the mixture was slowly heated to 80°C and maintained for 5 minutes. The mixture was then slowly heated to 150°C and maintained for 5 minutes. Finally, the mixture was heated to 180°C and maintained for 20 minutes. The mixture was naturally cooled to 160°C. After stopping stirring for a period of time, the mixture was cooled to room temperature. Argon protection was maintained throughout the process. PVP and other additives were removed by multiple high-speed centrifugation. After washing and drying, nanosilver wires with a diameter range of 10-30 nm and a length range of 10-100 μm were obtained.
[0015] Furthermore, an overcoat hardening coating is provided on the side of the nano silver wire conductive layer away from the substrate layer, and the compound containing active polymerizable functional groups in the glue of the overcoat hardening coating is a trifunctional (meth) acrylate monomer, a tetrafunctional (meth) acrylate monomer, and a pentafunctional (meth) acrylate monomer. The trifunctional (meth) acrylate monomer is pentaerythritol tri(meth) acrylate, trimethylolpropane tri(meth) acrylate, glycerol tri(meth) acrylate, tri(meth) acrylate tri(2-hydroxyethyl) isocyanate tri(meth) acrylate, or tri(2-hydroxyethyl) isocyanate tri(meth) acrylate; the tetrafunctional (methacrylic monomer is) pentaerythritol tetra(meth) acrylate or di(trimethylol)propane tetra(meth) acrylate; the non-functional (methacrylic monomer) is di(poly)pentaerythritol penta(methacrylate). The polymerizable resin is methyl methacrylate. The photoinitiator is one of 1-hydroxycyclohexyl benzophenone, 2,2-dimethoxy-2-2 phenylacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 4-chlorobenzophenone, 4,4-dimethoxybenzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, or a mixture of two or more thereof. The content of the active functional group polymerizable compound contained in the glue of the overcoat hardening coating is 0.1%-10%. If the content of the active functional group polymerizable compound is too low, it is not easy to better improve the adhesion of the nanosilver to the substrate, and the alcohol wiping resistance is poor, which will eventually cause a decrease in the yield of the actual back-end production. If the content is too high, the cross-linking effect is not sufficient during UV curing, which will reduce the adhesion of the overcoat hardening coating to the substrate, thereby reducing the adhesion of the nanosilver conductive layer on the substrate, and the alcohol wiping resistance is poor, which will eventually cause a decrease in the actual back-end production. It is important that the film thickness of the glue of the overcoat hardening coating is less than the "thickness" of the nanosilver conductive layer adsorbed on the substrate, otherwise it will affect the conductive performance of the nanosilver conductive layer.
[0016] Furthermore, the overcoat hardening coating contains a compound having an active polymerizable group, wherein the group includes one or more of a hydroxyl group, a carboxyl group, an amino group, a sulfonic acid group, a nitro group and a mercapto group.
[0017] Furthermore, the glue of the anti-glare layer comprises:
[0018] Organic resin: 20-40%
[0019] Inorganic particles: 2-10%
[0020] Leveling agent: 0.5-5%
[0021] Initiator: 1-3%
[0022] Solvent: 42-76.5%;
[0023] The organic resin contains a total organic resin content of 20-40%, and the organic resin includes one or more of dipentaerythritol tetra(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and polyurethane acrylate. The inorganic particles are surface-treated silica particles with a particle size of 5 μm and surface-treated silica particles with a particle size of 100 nm, with a total content of 2-10%. The content of the two particles of different particle sizes can be adjusted, and the ratio between the former 5 μm particles and the latter 100 nm particles is 99 / 1 to 5 / 95. The leveling agent is BYK-3760. The initiator includes initiator 184 and TPO, and the ratio between the two can be adjusted.
[0024] The surface of 5 μm silica particles was treated as follows:
[0025] 2 grams of silica nanoparticles (average diameter 5 μm) were purchased from the market, put into 50 mL of anhydrous xylene solvent, 1 mL of tridecafluorooctylsiloxane and 2 mL of acrylsiloxane organic matter were added, refluxed for 5 hours, and then the hydrophobic group tridecafluorooctyl and the organic matter containing unsaturated bonds were grafted onto the surface of the silica particles. Finally, the silica particles treated with fluorine-containing compounds were obtained by drying at 120 degrees Celsius for 10 hours.
[0026] The surface of 100 nm silica particles was treated as follows:
[0027] 2 grams of silica nanoparticles (average diameter 100 nm) were purchased from the market, put into 50 mL of anhydrous xylene solvent, 1 mL of tridecafluorooctylsiloxane and 2 mL of acrylsiloxane organic matter were added, refluxed for 5 hours, and then the hydrophobic group tridecafluorooctyl and the organic matter containing unsaturated bonds were grafted onto the surface of the silica particles. Finally, the silica particles treated with fluorine-containing compounds were obtained by drying at 120 degrees Celsius for 10 hours.
[0028] The silica particles treated by the above method are not easy to aggregate during actual use. The unsaturated double bonds on the surface of the particles can participate in the chemical reaction of the organic resin, so that the particles can be well "embedded" into the coating and the surface of the coating, increasing the hardness of the coating and the ability to resist external forces. The 100nm silica particles can better fill the gaps at the junction of the 5μm particles and the resin and the gaps between particles with larger particle sizes, reducing the surface roughness of the anti-glare coating and providing a guarantee for the uniformity of the thickness of the low refractive index coating layer.
[0029] Furthermore, the glue of the low refractive index layer comprises:
[0030] Organic resin: 5-20%
[0031] Inorganic particles: 0.5-10%
[0032] Leveling agent: 0.5-5%
[0033] Initiator: 1-3%
[0034] Solvent: 62-93%;
[0035] The organic resin comprises one or more of dipentaerythritol tetra(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and polyurethane acrylate, and the inorganic particles are hollow silica particles that have been surface treated.
[0036] The hollow silica particles are specifically processed as follows: 2 grams of hollow silica nanoparticles (average diameter 15nm) are purchased from the market, put into 50mL of anhydrous m-xylene solvent, 1mL of 13fluorooctylsiloxane and 2mL of propylene siloxane organic matter are added, refluxed for 5 hours, and then the hydrophobic group 13fluorooctyl and the organic matter containing unsaturated bonds are grafted onto the surface of the silica particles, and finally 120 degrees Celsius are dried for 10 hours to obtain surface-treated silica particles. The surface of the silica particles processed by this method contains fluorine compounds, which further reduces the refractive index, while reducing the aggregation between the silica particles, and the particle surface also contains unsaturated double bond organic matter, which participates in the reaction between organic resins, so that particles can be well embedded in the middle of the coating, increasing the ability of the coating surface to resist external forces. The refractive index of the coating is further adjusted by adjusting the content of inorganic particles in the organic resin and the surface fluorine content of inorganic particles. If the content of the processed hollow inorganic particles is too low, the refractive index of the low refractive index layer will increase; if the particle content is too high, the particles will easily aggregate; the leveling agent is BYK-3760, which can make the glue wet well on the surface of the substrate and reduce the number of coating crystal points; the initiators include 184 and TPO, and the ratio between the two initiators can be adjusted.
[0037] Furthermore, the substrate is selected from PET, TAC, PC, PEN, PI, PAI, COP, PEN, and the thickness of the substrate is in the range of 30-180 μm. Beneficial Effects
[0038] The technical solution of the present invention reduces production costs and improves production efficiency, realizes a nano silver wire conductive film with anti-glare and anti-reflection functions through an optical film, improves consumers' user experience, and can prepare a nano silver wire conductive film with anti-glare and anti-reflection functions. The anti-glare coating increases the diffuse reflection of light, and the anti-reflection coating of appropriate thickness reduces the reflection of light by using the interference principle of light. The combined effect of the two allows the human eye to observe the film surface from all angles, with uniform brightness, no "glare", and no sharp "dazzling" phenomenon. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the nanosilver wire conductive film of Example 1, wherein 1 is a substrate, 2 is a nanosilver wire conductive layer, 3 is an anti-glare layer, and 4 is a low refractive index layer. DETAILED DESCRIPTION
[0040] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0041] Example 1
[0042] The glue of the anti-glare coating (5μm particle size surface-treated silica particles with a content of 7%, 100nm particle size surface-treated silica particles with a content of 3%) is coated on a 125μm PET substrate, and after heat drying and UV curing, an anti-glare coating with an optical thickness of 7μm is formed. The glue of the low refractive index layer is coated on the anti-glare coating, and after heat drying and UV curing, an anti-reflective coating with a thickness of 100nm is formed. The glue of the nano silver wire conductive layer and the glue of the overcoat hardening coating are respectively coated on the other side of the substrate, and after heat drying and UV curing, a nano silver wire conductive film (30Ω) with both anti-glare and anti-reflective functions is finally formed.
[0043] The anti-glare coating glue contains an organic resin, wherein the organic resin includes 10% of dipentaerythritol tetra(meth)acrylate, 10% of tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and 10% of polyurethane acrylate; 5μm The content of silica particles with a particle size of 7%, the content of surface-treated silica particles with a particle size of 100 nm is 3%, the total content of inorganic particles is the sum of the two is 10%, the content of leveling agent BYK-3760 is 2%, the content of initiator 184 is 2%, the content of initiator TPO is 1%, and the rest is organic solvent.
[0044] The glue of the low refractive index layer comprises an organic resin, wherein the organic resin comprises 3% of dipentaerythritol tetra(meth)acrylate, 2% of tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, 5% of polyurethane acrylate, 10% of silica particles, 1% of the leveling agent BYK-3760, 2% of the initiator 184 and 1% of TPO, and the rest is an organic solvent.
[0045] The nano silver wire conductive layer has an average diameter of 20 nm and an average length of 50 μm;
[0046] The content of polymerizable compounds with active functional groups in the glue of the overcoat hardening coating is 5%, including 3% of tri(2-hydroxyethyl)isocyanate tri(meth)acrylate and 2% of pentaerythritol tri(meth)acrylate. The polymerizable resin is methyl methacrylate, with a content of 20%.
[0047] Example 2
[0048] Different from Example 1, the content of the inorganic particles in the anti-glare layer is 2%, wherein the ratio between the particles with a size of 5 μm and the particles with a size of 100 nm is 99:1.
[0049] Example 3
[0050] Different from Example 1, the content of the inorganic particles in the anti-glare layer is 10%, wherein the ratio between the particles with a size of 5 μm and the particles with a size of 100 nm is 1:99.
[0051] Example 4
[0052] Different from Example 1, in the low refractive index layer, the content of the inorganic particles is 0.5%, and the refractive index is 1.45.
[0053] Example 5
[0054] Different from Example 1, the low refractive index layer has a thickness of 80 nm.
[0055] Example 6
[0056] Different from Example 1, the low refractive index layer has a thickness of 120 nm.
[0057] Example 7
[0058] Different from Example 1, the anti-glare coating has a thickness of 5 μm.
[0059] Example 8
[0060] Different from Example 1, the anti-glare coating has a thickness of 15 μm.
[0061] Example 9
[0062] Different from Example 1, the glue of the overcoat hardening coating contains 0.1% of active functional group polymerizable compounds, including 0.5% of tri(2-hydroxyethyl) isocyanate tri(meth)acrylate and 0.5% of pentaerythritol tri(meth)acrylate, and the polymerizable resin is methyl methacrylate, with a content of 30%.
[0063] Example 10
[0064] Different from Example 1, the glue of the overcoat hardening coating contains 10% of active functional group polymerizable compounds, including 5% of tri(2-hydroxyethyl)isocyanate tri(meth)acrylate and 5% of pentaerythritol tri(meth)acrylate, and the polymerizable resin is methyl methacrylate, with a content of 30%.
[0065] Comparative Example 1
[0066] Different from Example 1, no low refractive index layer is included.
[0067] Comparative Example 2
[0068] Unlike Example 1, no anti-glare coating was included.
[0069] Comparative Example 3
[0070] Different from Example 1, the glue of the anti-glare coating only contains 5 μm inorganic particles that have not been surface treated.
[0071] Comparative Example 4
[0072] Different from Example 1, the glue of the anti-glare coating only contains 100 nm inorganic particles that have not been surface treated.
[0073] Comparative Example 5
[0074] Different from Example 1, the content of inorganic particles in the glue of the low refractive index layer is 0.01%.
[0075] Comparative Example 6
[0076] Different from Example 1, the low refractive index layer has a thickness of 50 nm.
[0077] Comparative Example 7
[0078] Different from Example 1, the low refractive index layer has a thickness of 200 nm.
[0079] Comparative Example 8
[0080] Different from Example 1, the anti-glare layer has a thickness of 2 μm.
[0081] Comparative Example 9
[0082] Different from Example 1, the anti-glare layer has a thickness of 15 μm.
[0083] Comparative Example 10
[0084] Different from Example 1, the glue of the overcoat hardening coating does not contain any polymerizable compound with active functional groups.
[0085]
[0086] Table 1
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nano silver wire conductive film, characterized in that: It includes a substrate, a nano silver wire conductive layer, an anti-glare layer and a low refractive index layer; An overcoat hardening coating is provided on the side of the nano silver wire conductive layer away from the substrate layer; The thickness of the low refractive index layer is in the range of 80-120 nm; The glue of the anti-glare layer contains first inorganic particles and second inorganic particles, the first inorganic particles are surface-treated silica particles with a particle size of 5 μm, the second inorganic particles are surface-treated silica particles with a particle size of 100 nm, the total content of the first inorganic particles and the second inorganic particles accounts for 2%-10% of the total content of the glue of the anti-glare layer, and the mass ratio of the first inorganic particles to the second inorganic particles is 99 / 1 to 1 / 99; The glue of the overcoat hardening coating contains a compound with an active polymerizable group. The compound containing the active polymerizable functional group in the glue of the overcoat hardening coating is a trifunctional (meth)acrylate monomer, a tetrafunctional (meth)acrylate monomer, or a pentafunctional (meth)acrylate monomer. The group includes one or more of a hydroxyl group, a carboxyl group, an amino group, a sulfonic acid group, a nitro group, and a thiol group. The content of the active functional group polymerizable compound in the glue of the overcoat hardening coating is 0.1%-10%; The glue of the anti-glare layer comprises: 20-40% organic resin, 2-10% inorganic particles, 0.5-5% leveling agent, 1-3% initiator and 42-76.5% solvent; the organic resin comprises one or more of dipentaerythritol tetra(meth)acrylate, tri(2-hydroxyethyl)isocyanuric acid tri(meth)acrylate and polyurethane acrylate.
2. The silver nanowire conductive film according to claim 1, characterized in that: The anti-glare layer has a thickness ranging from 5 to 18 μm.
3. The silver nanowire conductive film according to claim 1, characterized in that: The refractive index of the low refractive index layer is in the range of 1.3-1.
45.
4. The silver nanowire conductive film according to claim 1, characterized in that: The diameter of the nano silver wires in the nano silver wire conductive layer is in the range of 10-30 nm, and the length is in the range of 10-100 μm.
5. The silver nanowire conductive film according to claim 1, characterized in that: The glue of the low refractive index layer comprises: Organic resin: 5-20% Inorganic particles: 0.5-10% Solvent: 62-93%; The organic resin includes one or more of dipentaerythritol tetra(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and polyurethane acrylate.
6. The silver nanowire conductive film according to claim 1, characterized in that: The substrate is selected from PET, TAC, PC, PEN, PI, PAI, COP, PEN, and the thickness of the substrate is in the range of 30-180 μm.
Citation Information
Patent Citations
Anti-dazzling optical laminate
CN101308220A
Conducting film integrated structure
CN101634918A
Ultra-soft low-resistance transparent conductive film and preparation method thereof
CN108630339A
Silver nanowire conducting film
CN211350127U